Epidemiological profile of poisoning patients in the emergency department of a tertiary care teaching hospital in South India - Srihari Cattamanchi; Ramakrishnan Trichur V.; Aditya Maddali (International Journal of Medical Research and Review, 2017)
Background: Poisoning is a global public health issue and one of the common causes for visiting an emergency department (ED). A high index of suspicion based on etiology and clinical features is required to diagnose different types of poisons and their compounds.Aims: To define the epidemiological profile of patients registered in the ED with complaints of ingestion of poison, and to identify different types of poisons consumed, the duration of hospital stay and mortality due to these poisons.Methods: A retrospective analysis of patients presenting to the ED with complaints of poisoning. All patients registered in the ED with complaints of consumption of poison were included in the investigation. Patient charts with snake bites or scorpion stings were excluded. The medical charts with a discharge diagnosis of Poisoning during the study period were identified using the ICD-10-CM diagnosis codes categories T36-T65. Data was collected in a preformatted questionnaire.Results: In this study, 317 patients were enrolled, with a female predominance of 54.8%. Thirty-one percent of the patients are 15 to 24 years old, and 11.35% are below five years. Thirty percent were students, 18.3% housewives and 6.62% were farmers, with 59.3% having access to poisons at their homes, 19.87% from the pharmacy and 14.9% from a neighborhood store. The intent of poisoning in 85.8% of the patients was suicidal. 34.7% patients ingested pesticides, 30.28% patients, presented with tablet overdose, 14.82% patients consumed rodenticides and insecticides, and 3.47% patients presented with oleander seed poisoning. About 32.17% of the patients were admitted to ICU. Nearly 53.94% patients were discharged within three days of hospitalization. The mortality rate due to poisoning was 4.1%.Conclusion: This research article defines the epidemiological profile of poisoning patients registered in the emergency department, along with the common poisons used, duration of hospital stay and mortality due to poisoning.